Some problems typically present in sociological justification and foundation: Notes on the theoretical debate regarding contemporary sociology - Mora, Maynor Antonio (2015)
In this paper some problems typically observed in contemporary sociological justification and foundation, as well as its implications, are discussed from a constructivist epistemological, pragmatic and evolutionary position. The central thesis proposed here is the need to reconsider archaeologically these problems (from the origin of the discipline and in the sense proposed by Foucault, i.e. from the reconstruction of the deep layers of our own contemporaneity). These problems should be reconsidered without forgetting the course of sociology and its historical background in modern times, specifically in the last century and a half of its historical development, in order to avoid the renewed imposition of common sense, sociological common sense and ideology, which in many cases are camouflaged under the technique or uncritical utopistics.